Lack of replication of seven pancreatic cancer susceptibility loci identified in two Asian populations - Campa, Daniele; Rizzato, Cosmeri; Bauer, Andrea; Werner, Jens; Capurso, Gabriele; Costello, Eithne; Talar-Wojnarowska, Renata; Jamroziak, Krzysztof; Pezzilli, Raffaele; Gazouli, Maria; Khaw, Kay-Tee; Key, Timothy J.; et al. (Cancer epidemiology, biomarkers & prevention, 2013)
Background: Two recent genome-wide association studies (GWAS) of pancreatic ductal adenocarcinoma (PDAC), conducted, respectively, in a Japanese and in a Chinese population, identified eight novel loci affecting PDAC risk. - Methods: We attempted to replicate the novel loci in a series of PDACs and healthy controls of European ancestry in the context of the newly formed PANcreatic Disease ReseArch (PANDoRA) consortium. We genotyped seven single-nucleotide polymorphisms (SNP): rs12413624, rs1547374, rs372883, rs5768709, rs6464375, rs708224, rs9502893 (one SNP identified in the Chinese GWAS is not polymorphic in Caucasians) in 1,299 PDAC cases and 2,884 controls. We also attempted stratified analysis considering the different stages of the disease and addressed the possible involvement of the selected SNPs on the survival of patients. - Results: None of the SNPs were significantly associated with PDAC risk if considering the overall population of the consortium. When stratifying for country of origin, we found that in the Polish subgroup, the G allele of rs372883 was statistically significantly associated with increased risk [OR, 6.40; 95% confidence interval (CI), 2.28-17.91]. However, the sample size of the subgroups was rather small; therefore, this result can be due to chance. None of the SNPs was associated with disease progression or survival. - Conclusions: None of the SNPs associated with PDAC risk in two Asian populations were convincingly associated with PDAC risk in individuals of European descent. - Impact: This study illustrates the importance of evaluation of PDAC risk markers across ethnic groups. Cancer Epidemiol Biomarkers Prev; 22(2); 320-3. ©2012 AACR.
Published Online: December 18, 2012
Gesehen am 09.02.2021